Realizacja Wytycznych Komitetu Ministrów Rady Europy w sprawie wymiaru sprawiedliwości przyjaznego dziecku w kontekście zapobiegania ekskluzji społecznej i prawnej nieletnich - Kusztal, Justyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The aim of the article is to present the legal status and the state of scientiﬁc research on the implementation of national policy on the protection of the rights of children forced to participate in court proceedings. It is based on a method of analysis of the content of formal documents and selected research reports in the years 2015–2018 concerning the issues of child protection in contact with the justice system. The analysis of the research reports has led us to the conclusion that it is necessary to prepare judges and the police for the interrogation of children, but also to prepare them for contact with the institutional justice system through competently organised education on children’s rights.
Keywords: ochrona praw dziecka; dobro dziecka; pedagogika; edukacja; przesłuchanie